Cultural Approach to Literary Translation - Mahmoud, Mohamed Sidi Mohamed Sidi (Journal of Humanities & Social Sciences, 2023)
The cultural turn elaborated by Susan Bassnett, Andre Lefevere and Laurence Venuti is useful in the analysis of literary translation. It turns translation from the word level to the text level, with a consideration of the social, historical, cultural and religious contexts within which the process of translation is framed. In fact, their approach is a paradigmatic shift in translation studies because it recognizes the central position of culture in the process and analysis of translation. However, their framework remains unpractical, for it does not offer tangible methods that can solve translation problems resulting from linguistic and cultural divergences between SL and TL. Thus, the article examines the theoretical models elaborated by pioneers of the cultural turn of translation studies, such as those of the Manipulation School ( )and Postcolonial Theory. In addition, this article discusses Venuti’s foreignization of translation and its role in cultural representation and translation analysis.